New records of megachilid bees (Hymenoptera: Megachilidae) for Colombia - Guevara, Diego A. (2022)
The bee family Megachilidae consists of solitary species, some of which are important pollinators of cultivated plants. Although literature records indicate the existence of about 50 species of 10 genera of megachilid bees in Colombia, taxonomic studies are lacking and thus limited information is available on their identity as well as their distribution in the country. Herein, we provide new geographical records for the following ten species: Anthidium sanguinicaudum Schwarz, Chelostomoides otomita (Cresson), Hoplostelis bilineolata (Spinola), Megachile amparo Gonzalez, M. kalina Gonzalez et al., M. lorenziensis Mitchell, M. moderata Smith, M. simillima Smith, Pseudomegachile lanata (Fabricius), and Stelis costaricensis Friese. We report M. kalina for the first time for the country.